Proposal for an absorption refrigeration system driven by exhaust gases from diesel generators for ice production in the Amazon - Figueiredo Vinente, Lucas; Moreira Rodrigues, Vicente (Latin American Journal of Energy Research, 2022)
The present work proposes a thermodynamic analysis tool to design absorption refrigeration systems having as a hot source thermal waste from ship engines or motor-generators that supply electricity in riverside communities in the Amazon. The scarcity of electric energy in this region is a limiting factor in the conservation of fish, usually done with the use of ice, and since this is produced by a cycle that consumes electricity intensively, a viable alternative can be introduced, allowing the use of electric energy to another purpose. In this context, the analysis based on first law of thermodynamics is made for an absorption refrigeration system driven by exhaust from diesel generators. Mass, energy, and concentration balances were modeled by the author, through the Engineering Equation Solver (EES) software, the non-explicit properties were determined, thus avoiding resorting to imprecise diagrams, in the end, a linear system of equations that is solved in Microsoft Excel® software to find the variables of interest. The work attested, in accordance with the first law of conservation of thermodynamics, to the possibility of using exhaust and also estimated the amount of ice that would be produced.Keywords: Absorption cooling, Fish, Ice, Exhaust, Riverside community.